Role Institution Empowerment Village Communities (LPMD) In Village Development In Purbalingga District - Suci Laswono, Rukmawan (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
According to Article 94 of Law Number 6 of 2014 concerning Villages, Villages utilize existing Village community institutions to assist in implementing the functions of Village Government administration, Village development, Village community development, and Village community empowerment. The aim of this research is to explain and analyze the role of community empowerment institutions (LPM) in planning and implementing development in Karangklesem Village, Kutasari District, Purbalingga Regency. Researchers used descriptive qualitative research methods and had a total of 8 informants. Data collection techniques consist of literature study, interviews, and observation. The data analysis techniques used include data collection, data reduction, data presentation and verification stages. The results of the research concluded that: 1). The role of Community Empowerment Institutions (LPM) in Community Empowerment in Karangklesem Village, Kutasari District, Purbalingga Regency has been carried out well; 2). The obstacles faced by Community Empowerment Institutions in empowering communities in Karangklesem Village, Kutasari District, Purbalingga Regency include: a). LPM in participatory development planning in Buniseuri Village does not yet have a platform to accommodate community aspirations, thoughts/ideas/ideas that can make it easier to plan and prioritize development needs in Karangklesem Village, Kutasari District, Purbalingga Regency. 3). To overcome these various obstacles, the following efforts were made: a). LPM's efforts to plan development in a participatory manner in Karangklesem Village, Kutasari District, Purbalingga Regency are by holding various meetings with residents using various existing special facilities.